ANALISIS FAKTOR PRODUKSI ALAT TANGKAP PAYANG DI PELABUHAN PERIKANAN PANTAI CAROCOK TARUSAN KABUPATEN PESISIR SELATAN SUMATERA BARAT - Junaidi Alvi Rahmah (Jurnal Sosial Humaniora Sigli, 2020)
Payang is one of fishing gear commonly used by fisherman after lift net at Pelabuhan Perikanan Pantai (PPP) Carocok Tarusan of Pesisir Selatan District. This research aims to describe the catch unit of payang and analyze what factors affect production that produced by Payang. This research used census method by taking data of all Payang fishing gear at PPP Carocok Tarusan. The anlyze used as multiple linear regression and data processing entirely used statistical application SPSS version 22.0 with Enter method. Payang fishing gear at PPP Carocok Tarusan is operated by boat 5 GT and payang construction on left wing (left and right) is 20-25 meters, the net body is 10-20 meters, cod end as the spot for collecting fish catch has 5-8 meters, head rope and ground rope is 100 meters, and selambar strap for drawing fishing gear has 200 meters in lenght. Based on results processed with SPSS were obtained equation of multiple linear regression function on Payang fishing gear at PPP Carocok Tarusan as follow: Y = -58.747 + 11.625X1 + 4.707X2 - 13.244X3 - 1.644X4 + 5.915X5 + 23.693X6. Analysis of t-test showed that production factor of Payang fishing gear which has positive effect on the catch result are the length of trip on fishing (X1), the amount of fuel (X2), and setting (X6). Keywords: Payang, factors of production, regresi berganda, pesisir selatan